Comparison of two new species of astogloia Bacillariophyceae) with other small members of section Ellipticae - Pennesi, Chiara; Poulin, Michel; Hinz, Friedel; Romagnoli, Tiziana; de Stefano, Mario; Totti, Cecilia (Phytotaxa, 2013)
In this study, seven Mastogloia species belonging of the section Ellipticae are morphologically described through scanning electron microscopy, including two new taxa M. matthaei and M. stellae. They were collected as epiphytes on seagrasses from several tropical (Indonesia), subtropical (Egypt, Greece, Republic of Malta, Turkey) and temperate (Slovenia, Italy) regions of the world. All these species show typical characters of the Hustedt’s section Ellipticae: elliptical valve outline, a flat valve surface and rounded apices. Moreover, this study provides novel information on the frustule ultrastructure and gives update of their current geographical distribution. Some nomenclatural inconsistencies have been resolved with the typification of M. ovulum and the related species, M. emarginata, from the original Miang Besar material in the Hustedt collection.